2021
DOI: 10.3390/technologies9040089
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun PVP/TiO2 Nanofibers for Filtration and Possible Protection from Various Viruses like COVID-19

Abstract: In this study, TiO2 nanofibers were prepared with Polyvinylpyrrolidone (PVP) polymer using sol-gel method via electrospinning technique. Owing to the advantages of small fiber diameter, tunable porosity, low cost, large surface to volume ratio, structure control, light-weight, and less energy consumption, electrospun nanofibers are evolving as an adaptable material with a number of applications, in this case for filtration and environmental/virus protection. Different samples of TiO2/PVP nanofibers have been p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Nanofibers are produced by electrospinning, which is based on the drying of a thin liquid jet that is formed from a drop of polymer solution in a strong electric field [19] and are used in numerous applications [20,21]. They also represent an effective material for delivering different types of drugs to the nasal, oral, and vaginal mucosa [22], while at the same time, they protect drugs from environmental factors [23].…”
Section: Introductionmentioning
confidence: 99%
“…Nanofibers are produced by electrospinning, which is based on the drying of a thin liquid jet that is formed from a drop of polymer solution in a strong electric field [19] and are used in numerous applications [20,21]. They also represent an effective material for delivering different types of drugs to the nasal, oral, and vaginal mucosa [22], while at the same time, they protect drugs from environmental factors [23].…”
Section: Introductionmentioning
confidence: 99%
“…This is in response to encounter COVID-19, where nano-filtered face mask was developed with nanofibers (in the diameter range of 100-500 nm) arranged in orthogonal/unidirectional directions to relieve the challenges. For instance, PVP/TiO 2 nanofibers have been electrospun for potential application toward filtration and environmental remediation com/ compa ny/ beiji ng-landi ngji-engin eering-tech-co. ,-ltd China [140]. In addition, antimicrobial nanoparticles were also introduced into the nanofibers to increase the filtration efficacy and which is possible only through electrospinning.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The nanoporosity (1.44–4.08 nm) of the electrospun nanofibers was confirmed by BET assay and believed to be effective for protective masks as well as air and water filtration of viruses. 169…”
Section: Coinage Metals and Their Antiviral Abilitymentioning
confidence: 99%
“…The nanoporosity (1.44-4.08 nm) of the electrospun nanofibers was confirmed by BET assay and believed to be effective for protective masks as well as air and water filtration of viruses. 169 Similarly, ZnO-based nanomaterials have been reported to be effective against SARS-CoV-2 as ZnO-based surfaces and coatings minimize the infectivity of SARS-CoV-2 to about 99.9 in 1 h. 170,171 Gouda and team members studied the effect of hesperidin-mediated ZnO NPs against hepatitis A virus and thought these particles might be effective against COVID-19. This study revealed the antiviral potential of hesperidinmediated ZnO NPs compared to hesperidin alone.…”
Section: Other Metal-based Nanomaterials For Sars-cov-2mentioning
confidence: 99%